Nueva dimensión jurídica de la violencia intrafamiliar y su efectividad en la tutela constitucional - García Aguirre, Jaime Jarry (2015)
Domestic violence causes irreparable damage to both the victim and the aggressor, because, in many cases, the person exercising violence before was also a victim. Usually, this kind of violence does not occur in isolation, but follows a consistent pattern over time. Main taxpayers are women, and children and dependents. All forms of family violence are an abuse of power and trust. Given the complexity and variety of the phenomenon is very difficult to know their global dimensions. The psychological type, also known as emotional, is a form of abuse and is categorized. It should be noted that gender violence has been a long-debated issue internationally and this product has been formulated a set of instruments (treaties, conventions, action plans, declarations guidelines) to eradicate violence gender against women. In the case of Ecuador, as evidenced by the statistics, violence is a structural problem that affects the quality of life of women and which must be faced by the state policy level and at the level of the justice system.